HUBUNGAN HUKUM ANTARA DRIVER DENGAN PERUSAHAAN BERBASIS APLIKASI STUDI PERBANDINGAN NEGARA INDONESIA DENGAN NEGARA BAGIAN CALIFORNIA AMERIKA SERIKAT - Resky Pradhana Romli (Universitas Harapan Medan, 2022)
PT Applications Karya Anak Bangsa (Gojek) is a Limited Liability Company with a license as a technology company to provide applications but the online motorcycle taxi application is used for transportation services whose regulations for online transportation do not have strong legal certainty. Application companies are not required to provide